The Future PoF in Energy Industry - Amin E.P.P.; Lee H.J.; Ker P.J.; Jamaludin M.Z.; Awang R.; Yusof F.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Optical fibers; Electrical isolation; Energy industry; Fiber systems; Optical power; Power; Power distributions; Power over fiber; Power-distribution system; Power-over-fiber; Powerloss; Optical cables